Robert K. Merton sociology of science and sociology as science - Calhoun, Craig J., 1952-; ebrary, Inc. (New York : Columbia University Press, 2010)
"Robert K. Merton (1910-2003) was one of the most influential sociologists of the twentieth century, producing clear theories and innovative research that continue to shape multiple disciplines. Merton's reach can be felt in the study of social structure, social psychology, deviance, professions, organizations, culture, and science. Yet for all his fame, Merton is only partially understood. He is treated by scholars as a functional analyst, when in truth his contributions transcend paradigm.
Gathering together twelve major sociologists, Craig Calhoun launches a thorough reconsideration of Merton's achievements and inspires a renewed engagement with sociological theory. Merton's work addressed the challenges of integrating research and theory. It connected different fields of empirical research and spoke to the importance of overcoming divisions between allegedly pure and applied sociology. Merton realized the value of sociological methods that respect the institutional analysis of science and knowledge. By bringing together different aspects of his work in one volume, Calhoun illuminates the interdisciplinary& -and unifying& -dimensions of Merton's approach, while also advancing the intellectual agenda of an increasingly vital area of study."--BOOK JACKET.
On Merton's legacy and contemporary sociology / Craig Calhoun -- Reflections on a common theme : establishing the phenomenon, adumbration, and ideal types / Alejandro Portes -- Mechanisms of the middle range / Charles Tilly -- Eliding the theory/research and basic/applied divides : implications of Merton's middle range / Robert J. Sampson -- The contributions of Robert K. Merton to culture theory / Cynthia Fuchs Epstein -- Culture and uncertainty / Viviana A. Zelizer -- "Paradigm for the sociology of science" / Thomas F. Gieryn -- A critical reconsideration of the ethos and autonomy of science / Aaron L. Panofsky -- Merton, Mannheim, and the sociology of knowledge / Alan Sica -- The ethos of science and the ethos of democracy / Ragnvald Kalleberg -- Merton's sociology of rhetoric / Peter Simonson -- On sociological semantics as an evolving research program / Harriet Zuckerman -- How Merton sociologizes the history of ideas / Charles Camic.
Includes bibliographical references and index.
Electronic reproduction.
Keywords: Merton, Robert King, -- 1910-2003.; Sociologists -- United States; Sociology -- United States; Science -- Social aspects; Science -- Philosophy; Electronic books